An optical simulation algorithm based on ray tracing technique for light absorption in thin film solar cells - Byun, Seok-Joo; Byun, Seok Yong; Lee, Jangkyo; Kim, Jae Wan; Lee, Taek Sung; Kim, Won Mok; Park, Young Kyu; Cho, Kyuman (ELSEVIER SCIENCE BV, 2011)
Solar cells, especially thin film solar cells, utilize rough surfaces actively in order to improve light trapping efficiency. In this study, we propose a new optical simulation method, which is capable of taking into consideration the realistic surface and interface morphology. The proposed simulation algorithm is based upon a non-sequential ray tracing technique, and direct calculation of the optical absorption energy is performed by separating the light passing through medium into the coherent part and the incoherent part in the course of non-sequential ray tracing throughout the whole region of solar cell structure. It was shown that the new method can give more accurate estimation of the absolute absorption energy in the individual layer when applied for a thin film Si solar cell structure with rough surface of bidirectional scattering distribution function. Furthermore, the proposed algorithm was proved to be very effective in analyzing solar cells with complex geometry like concentrator photovoltaic system, which necessitates the combination of coherent and incoherent calculation. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: ZNO-AL; SILICON; SCATTERING; MODEL